IMPROVING STUDENTS’ WRITING ACHIEVEMENT ON RECOUNT TEXT THROUGH PEER RESPONSE TECHNIQUE - Muhammad Guntar; Masitowarni Siregar (Universitas Negeri Medan, 2013)
The objective of this study is to improve the students’ speaking The main objectiveof this study is to know how effective the use of Peer Response Technique in teachingwriting recount texts is. This study was conducted under the consideration that thestudents often get difficulties in retelling events in their own activities. In order toachieve the objective of the study, the writer designed an action research. The subjectsof this study was the first grade students of SMA An-Nizam Medan. The number of thesubjects of this study was 27 students. During the research, the students becoming thesubjects were taught by using Peer Response technique in teaching writing recounttexts. There were two cycles in this action research. Each cycle consisted of four phases.Before giving treatments in those two cycles, the students were given pre-test. Aftereach treatment in each cycle, the students were tested. And the last, they were givenpost-test and questionnaire. The result of this research showed that the students’ abilityin writing recount texts improved after a series of treatments given in the cycles. It canbe seen by comparing the means of their tests. The mean score for the pre-test was56.96, the mean score for test 1 was 69,85 while the mean score for the post-test was78,11. It is clear that after applying Peer Response Technique in each treatment, themean of each test improves and gets better. The use of Peer Response technique is oneof the ways to make students interest in studying English especially writing recounttext.